Cardiomyopathy of Friedreich Ataxia. (17th July 2013) - Weidemann, Frank; Störk, Stefan; Liu, Dan; Hu, Kai; Herrmann, Sebastian; Ertl, Georg; Niemann, Markus
Abstract: Friedreich's ataxia is a rare hereditary, predominantly neurologically defined multisystem disorder of mitochondrial function. Although the gene defect has been identified, the precise pathophysiology of the deficient mitochondrial protein, frataxin, is unknown. Besides the characteristic features of spinocerebellar ataxia the heart may also be affected, and patients may experience a hypertrophic cardiomyopathy eventually progressing toward heart failure and death. So far, research focused on the neurological aspects and little attention has been paid to better characterize and understand the cardiac involvement in Friedreich's ataxia. For that, a better understanding of longitudinal progression, cardiac complications and long‐term cardiac outcome is warranted. In addition, the clinician should be familiar with the therapeutic option in Friedreich cardiomyopathy. This review discusses important clinical and diagnostic features of the cardiomyopathy in Friedreich's ataxia and potential therapeutic developments.